Occupational diseases in Murmansk Oblast: 1980–2010 - Dudarev, Alexy A.; Talykova, LV; Odland, Jon Øyvind (International Journal of Circumpolar Health, 2013)
Background. Official statistics tend to underestimate the incidence of occupational disease (OD) nationally and regionally in Russia. Objectives. The general aim was to obtain an accurate estimate of ODs in Murmansk Oblast in 1980 2010 and to determine the rate of specific types of ODs among cohorts of workers who had been exposed to the hazardous factors causing the disease. Materials and methods. Data were retrieved from the Murmansk Oblast ODs database for the oblast and 2 enterprises Apatite JSC and Kolskaya MSC which contributed to more than half of the ODs in the oblast in 1980 2010. The total number of ODs and 5 specific categories (musculoskeletal, respiratory, nervous diseases, hearing loss and vibration disease) were analysed. Results. The total rate of ODs among workers of main shops in both enterprises who were actually exposed to harmful factors were extremely high: the rate for Apatite JSC was 25 times higher than in Russia and 15 times higher than in Murmansk Oblast, while the rate for Kolskaya MSC was about 30 and 20 times greater than in Russia and in Murmansk Oblast, respectively; in the 2000s the difference reached 100 150 times. The rise in reported ODs in both enterprises corresponded to the time when intensive medical examinations were conducted by the Kola Research Laboratory for Occupational Health (KRLOH) in Kirovsk. A similar pattern was also observed for the sub-categories of musculoskeletal, respiratory, nervous diseases, hearing loss and vibration disease. It is likely that the true burden of OD is even higher due to misdiagnosis, reluctance of workers concerned about job security to present for care and the lack of reliable information on working conditions needed to establish a causal link between disease and occupational exposure. Conclusions. As with many other regions across Russia, ODs in Murmansk Oblast are grossly underestimated. Serious problems exist in the Russian occupational health care system and the collection of occupational health statistics that require urgent, ...